2021
DOI: 10.13057/biodiv/d221217
|View full text |Cite
|
Sign up to set email alerts
|

Arthropods discovered in lower and upper pitchers of Nepenthes at Rampa-Sitahuis Hill, North Sumatra, Indonesia

Abstract: Abstract. Tarigan MRM, Corebima AD, Zubaidah S, Rohman F. 2021. Arthropods discovered in lower and upper pitchers of Nepenthes at Rampa-Sitahuis Hill, North Sumatra, Indonesia. Biodiversitas 22: 5358-5366. This research aimed to identify the families of arthropods trapped in the upper and lower pitchers of Nepenthes in Rampa Sitahuis Hill Area, North Sumatra, Indonesia. This descriptive qualitative research used an experimental method of data analysis. The arthropods were obtained from the upper and lower pitc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 62 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…In addition to the morphological characteristics of the pitcher and the quantity of liquid in it, the position of pitchers could also affect the diversity of trapped prey. Therefore, flying insects are most commonly found in the upper pitchers of Nepenthes [4,18]. In this study, the upper pitchers are visited more frequently by flying insect orders such as Blattoidae, Coleoptera, Diptera, Hemiptera, Orthoptera, and Hymenoptera (figure 4).…”
Section: Composition Of Prey Found In Nepenthes Pitchersmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition to the morphological characteristics of the pitcher and the quantity of liquid in it, the position of pitchers could also affect the diversity of trapped prey. Therefore, flying insects are most commonly found in the upper pitchers of Nepenthes [4,18]. In this study, the upper pitchers are visited more frequently by flying insect orders such as Blattoidae, Coleoptera, Diptera, Hemiptera, Orthoptera, and Hymenoptera (figure 4).…”
Section: Composition Of Prey Found In Nepenthes Pitchersmentioning
confidence: 73%
“…Family Culicidae (order Diptera) trapped in the sampled pitchers were mosquito larvae. Mosquito larvae were able to survive in the pitcher fluid with a pH of 2.8-4.9 [18]. Some other Diptera larvae, such as Nepenthosyrphus (family Syrphidae), Dasyhelea (family Ceratopogonidae), and the larvae of family Empididae, might also be found in the pitchers of Nepenthes.…”
Section: Composition Of Prey Found In Nepenthes Pitchersmentioning
confidence: 99%
“…The results of research on insects at the bottom and top of the five species of Nepenthes in North Sumatra, the highest number of individual insects found in Nepenthes was from the Hymenoptera order (family Formicidae) 16 . While the results of research on Gunung Kunyit Forest also found Hymenoptera which was found in Nepenthes pitcher plants.…”
Section: Discussionmentioning
confidence: 95%
“…Nepenthes are widely distributed in Indonesia, with 32 species recorded in Kalimantan between 2005 and 2014, 29 species in Sumatra, ten Sulawesi, nine in Papua, four in Maluku, and two species in Java. (Handayani 2017;Cheek and Jebb 2013;Dančák et al 2022;Tarigan et al 2021). Nepenthes also spread from the east of Madagascar to New Caledonia, southern China, and several small remote islands in the Western Pacific and Malesiana (Gaume et al 2016;Mansur et al 2021;Nerz and Koch 2018;Tarigan et al 2021;Yulita and Mansur 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(Handayani 2017;Cheek and Jebb 2013;Dančák et al 2022;Tarigan et al 2021). Nepenthes also spread from the east of Madagascar to New Caledonia, southern China, and several small remote islands in the Western Pacific and Malesiana (Gaume et al 2016;Mansur et al 2021;Nerz and Koch 2018;Tarigan et al 2021;Yulita and Mansur 2012).…”
Section: Introductionmentioning
confidence: 99%